Implementation of Public Policy in the Implementation of the Independent Curriculum at Bina Bangsa Serang University, Banten - Milah Hamdalah, Ratu (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The Freedom of Learning Independent Campus (Merdeka Belajar Kampus Merdeka) is an education policy introduced to improve the quality of learning in Indonesia. The main purpose of this policy is to provide freedom in choosing, accessing, and managing their own learning process. One of the universities that implements this policy is Bina Bangsa University. The purpose of this study is to determine the extent to which the implementation of the Independent Campus has been implemented at Bina Bangsa University. The research method used is a qualitative method with a case study approach. Data was collected through in-depth interviews with key informants, participant observation, and documentation. The results showed that the implementation of the Independent Curriculum policy at Bina Bangsa University has gone well.